Penanganan Kasus Latah dengan Metode Counting Backward: Studi Kasus Tunggal - Hikmatun Sadiah; Nur Fitri; Tangginas Tangginas (22039) (Jurnal Terapi Wicara, 2024)
Latah syndrome can be understood as a communication disorder because as a result of talkativeness the verbal interaction process does not run normally, impairs the smoothness of communication, and affects the individual's ability to interact effectively with other people. Latah is characterized by an excessive response to certain stimuli, which often interferes with the sufferer's daily life. Latah is a syndrome that is quite common in Indonesia, especially among women, but despite its high prevalence, the intervention methods used to treat latah have not been studied in depth.